The Role of Virtual Reality in Enhancing Students’ Learning - Alshammari, Sultan Hammad (International Journal of Educational Technology and Learning, 2019)
The globalization, innovation, and rapid spread of advanced technologies in different fields, including education, are a recent trend. Virtual reality (VR) is one emerging technology that has been used in recent years in medical training, military training, and other fields. It also presents several opportunities in the educational sector to support teaching and learning processes and thus deserves greater attention from educators and policy makers. The present paper reviews the huge role of Virtual Reality in supporting and enhancing students’ learning in four main areas: collaborative/cooperative learning, creative learning, problem-based learning, and role playing. Different types and categories of VR are also explored. Finally, some of the limitations associated with the implementation of VR, including its high cost, and possible solutions are discussed. Overall, VR presents several unique opportunities for enhancing teaching and students’ learning.